2014
DOI: 10.4161/hv.29553
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccine CV9103 and CV9104 for the treatment of prostate cancer

Abstract: Among currently available vaccine strategies for cancer, nucleotide-based vaccination is an appealing treatment modality. Curevacs' mRNA containing vaccines (RNActive Ò ) combine the beneficial properties of sufficient antigenexpression, autologous immune-stimulation and a high flexibility with respect to production and application. CV9103 and CV9104 are novel RNActive Ò -derived anticancer vaccines for the treatment of patients with prostate cancer. After successful phase I/II studies with documentation of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 47 publications
0
66
0
Order By: Relevance
“…[166][167][168] Antigen expression strongly depends on the ratio between protamine and mRNA. 169 This vaccine platform has raised favorable immune activations against cancer and infectious diseases in both pre-clinical animal models and in patients. [169][170][171] Lipids and Polymers.…”
Section: Non-amplifying Mrna Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[166][167][168] Antigen expression strongly depends on the ratio between protamine and mRNA. 169 This vaccine platform has raised favorable immune activations against cancer and infectious diseases in both pre-clinical animal models and in patients. [169][170][171] Lipids and Polymers.…”
Section: Non-amplifying Mrna Vaccinesmentioning
confidence: 99%
“…169 This vaccine platform has raised favorable immune activations against cancer and infectious diseases in both pre-clinical animal models and in patients. [169][170][171] Lipids and Polymers. Both cationic lipids and polymers have been investigated as vehicles for mRNA vaccines in the past decades.…”
Section: Non-amplifying Mrna Vaccinesmentioning
confidence: 99%
“…It has been found to be highly immunogenic in patients with prostate and renal cancer in a phase I/II trial [142]; the phase II trial NCT02293707 is evaluating the immunological effects of GX301 in mCRPC patients who have achieved response or disease stability after first-line docetaxel-based chemotherapy. CV9103 and CV9104 are RNA vaccines encoding for PSA, prostate stem cell antigen, PSMA, and six transmembrane prostate epithelial antigens [143]. CV9103 was shown to be safe and well tolerated in a phase I/IIa study enrolling mCRPC patients [144]; 79% of 33 patients developed antigen-specific T cells and more than two-thirds of them developed immune responses to multiple antigens.…”
Section: Vaccinesmentioning
confidence: 99%
“…So far, the results have shown that mRNA‐based vaccines induce humoral and cellular immune responses and result in an increased survival rate. To date, there are two interesting clinical trials in progress, one for castration‐resistant prostate cancer and another for nonsmall cell lung cancer . Both studies showed that the application of RNActive® vaccines (from the company CureVac) to humans was safe .…”
Section: Applications Of Ivt Mrnamentioning
confidence: 99%